Al-Maqashid Syariah Performance in Islamic Bank: Al-Maqashid Syariah Performance in Islamic Bank - Lilly Anggrayni (AKASYAH: Jurnal Akuntansi, Keuangan dan Audit Syariah, 2022)
This study is aim to examined the effect of maqashid syariah performance. This study employed Maqashid Syariah Index and content analysis as the method of analysis. The Islamic Banks usually employed the conventional yardstick in measuring the IBs performance and firm value. Otherwise, this yardstick is not fit with the condition of IBs. Therefore this study suggests the usage of the IMSPM as the tool measurement of IBs performance, that more complete than the conventional yardstick. This study had important contribution for practitioners of IBs and also Islamic accounting researchers.